Study of the ethnic origin of the prothrombin gene (F2) in the admixed Venezuelan population. / Origen étnico del gen de la protrombina (F2) en la población venezolana. - Kanzler, Daniela; Marchi, Rita; Paradisi, Irene (Investigación Clínica, 2020)
Abstract. The prothrombin (coagulation factor II), codified by the F2 gene, is the precursor of thrombin that cleaves fibrinogen, leading to a blood clot formation. The F2 mutation 20210 G>A (c.*97G>A) is associated with prothrombin thrombophilia, and carriers have a higher than average risk for developing deep venous thrombosis. The 20210A variant is almost absent in populations other than Caucasoid European, and was not found in a Venezuelan population sample of 160 healthy individuals. To assess the possible ethnic origin of the F2 gene in our admixed population, four intragenic SNPs (rs2070850, rs2070852, rs2282686 and rs1799963), with different allelic frequencies according to ethnic groups, were studied and compared with the main 1000 Genomes Project super-populations. The results showed intermediate allelic frequencies in all the SNPs, without differentiating a single specific population, confirming the joint ancestral genetic contribution of the parental populations in Latin America: Spaniards, Africans and Amerindians. Our allelic frequency distribution of the F2 polymorphisms was closer to the AMR (American admixed) subset population of the 1000 Genomes Project. According to this ethnic composition, there is a low probability of detecting carriers of the risk allele 20201A in the Venezuelan healthy general population. Resumen. La protrombina (factor de coagulación II), codificada por el gen F2, es un precursor de la trombina, la cual escinde al fibrinógeno, conducente a la formación de un coágulo de sangre. La mutación F2 20210 G>A (c. * 97G> A) se asocia con trombofilia y los portadores tienen un riesgo superior al promedio de desarrollar trombosis venosa profunda. La variante 20210A está casi ausente en poblaciones distintas a la europea caucasoidea, y no se encontró en una muestra de 160 individuos sanos de la población venezolana. Para evaluar el posible origen étnico del gen F2 en nuestra población mezclada, se estudiaron cuatro SNP intragénicos (rs2070850, rs2070852, rs2282686 y rs1799963) con diferentes frecuencias alélicas, según los grupos étnicos y se compararon con las principales superpoblaciones del Proyecto 1000 Genomas. Los resultados mostraron frecuencias alélicas intermedias en todos los SNP, sin diferenciar una única población específica, lo que confirma la contribución genética ancestral conjunta de las poblaciones parentales en América Latina: españoles, africanos y amerindios. Nuestra distribución de frecuencias alélicas de los polimorfismos de F2 fue más parecida al subconjunto AMR (American admixed population) del Proyecto 1000 Genomas. De acuerdo con esta composición étnica, existe una baja probabilidad de detectar portadores del alelo de riesgo 20201A en la población general sana venezolana.